AN ANALYSIS OF FIGURATIVE LANGUAGE ON EFEK RUMAH KACA’S SONG LYRICS: SINESTESIA 2015 - Iqbal, Muhammad; Thamrin, Husni; Maulana, Angga; Rusmana, Erik (IPI Garut Press, 2022)
Figurative language is one kind of the language styles to make the expression and the message of the speaker or writer become clearer. Figurative language usually used in song lyrics. Sometimes, figurative languages existed in song lyrics can’t be understandable. One of the song lyrics that has a lot of figurative languages is songs from Sinestesia album by Efek Rumah Kaca. Therefore, this research is trying to analyze figurative languages existed in song lyrics on Efek Rumah Kaca’s album titled Sinestesia. The research is focused on analyzing type of figurative languages with its meaning by using Kennedy’s theory of classification of figurative language (1983) and Ogden and Richard’s theory of meaning (1923). Qualitative descriptive was the method that used for this research. The results of this research show that 4 type of figurative languages were found, which were 25 personifications, 18 metaphors, 15 overstatements, and 2 apostrophes with each of figurative language’s meaning is elaborated. Besides of it, the writer found that figurative languages existed in the Sinestesia album’s song lyrics has a connection to the song itself.